Analisis Prediksi Financial Distress Menggunakan Model Altman Z-Score, Springate, dan Zmijewski pada Perusahaan Manufaktur di BEI Periode 2020–2025 - Nabilla Maharani; Encep Saefullah; Arta Rusidarma Putra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Financial Distress remains a critical issue for manufacturing companies listed on the Indonesia Stock Exchange (IDX), reflected in recent delisting cases and substantial corporate losses. This study analyzes the prediction of Financial Distress using the Altman Z-Score, Springate, and Zmijewski models and examines whether the three models produce significantly different results when applied to the same sample. A quantitative comparative approach was used with a purposive sampling technique, yielding a final sample of fifteen large manufacturing companies across five IDX-IC sectors during the 2020–2025 period, or ninety firm-year observations. Secondary data were obtained from audited annual financial statements and analyzed through descriptive statistics, normality tests, correlation analysis, and the non-parametric Kruskal-Wallis test. The results show that the Altman Z-Score classifies 23.3 percent of observations as distressed, Springate 21.1 percent, while Zmijewski classifies none as distressed. The Kruskal-Wallis test confirms a statistically significant difference among the three models' median scores. These findings imply that model selection is not methodologically neutral, and stakeholders are advised to apply a multi-model approach, with the Altman Z-Score serving as the most conservative early-warning indicator.